2015
DOI: 10.1155/2015/361037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Indirect-ELISA Test forTrypanosoma evansiInfection (Surra) in Buffaloes and Its Application to a Serological Survey in Thailand

Abstract: Surra, caused by Trypanosoma evansi, is a neglected disease due to frequent subclinical evolution, especially in bovines in Asia. However, acute and chronic signs are regularly observed, with significant sanitary and economic impacts. In this study, we evaluated and applied an indirect-ELISA test for the detection of anti-T. evansi immunoglobulin G in buffaloes using antibovine conjugate. Based on buffalo reference sera from the Philippines, a two-graph receiver operating characteristics analysis (TG-ROC) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…The current study reported for the first time on the seroprevalence of T. evansi infection in bullfighting cattle. In general, the sensitivity and specificity of indirect-ELISA for trypanosomes are higher than 90% [ 9 ]. Previously, indirect ELISA using crude T. evansi antigen was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study reported for the first time on the seroprevalence of T. evansi infection in bullfighting cattle. In general, the sensitivity and specificity of indirect-ELISA for trypanosomes are higher than 90% [ 9 ]. Previously, indirect ELISA using crude T. evansi antigen was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In experimentally infected cattle, indirect ELISA showed satisfactory sensitivity and specificity [ 24 ]. Using the same indirect ELISA protocol, the seroprevalence levels of T. evansi infection in dairy cattle and buffaloes were 11.9% and 12.12%, respectively [ 8 , 9 ]. In comparison, seroprevalence in the current study was higher than in the previous studies, indicating that bullfighting cattle may be exposed to infection.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect ELISA T. evansi , as described by the OIE [17], has been used in several host species and was already validated for camels, cattle, buffaloes, and elephants in Thailand [12, 14, 15, 18]. The test used in this study was derived from previously published protocols with slight modifications and adaptation to horse samples.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, knowledge on the prevalence of T. evansi infection in its various host species is needed to better understand the relative roles of those different hosts in the epidemiology of surra . In recent times, epidemiological surveys of surra have been conducted in Thailand, in cattle, buffaloes and elephants [14, 15, 16]. However, equines have not yet been covered by these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation